A load balancing algorithm inspired by the honey bee behaviour to reduce waiting time in a perinatal network. (30th March 2022) - Lopes, Hudson Henrique De Souza; Oliveira, Ricardo Bruno Osés De; Rocha, Flávio Geraldo Coelho
This article proposes a solution to a problem of mixed-integer linear programming for efficient resource allocation in the admission and scheduling process of pregnant women to a perinatal network composed of two maternity hospitals with heterogeneous capacities. For this, a load balancing algorithm based on the metaheuristic of honey bee behaviour is used. It is shown, through the results obtained in the simulations, that the proposed algorithm reduces the mean turnaround time of the system and the waiting time for pregnant women who enter the perinatal network, in comparison with other load balancing algorithms, based on classic queue theory, that are found in the literature.